Minimally invasive esophagectomy for esophageal leiomyomatosis - Ryohei Shibata; Takeshi Saito; Keita Terui; Mitsuyuki Nakata; Shugo Komatsu; Tetsuya Mitsunaga; Gen Matsuura; Hidehito Shibasaki; Takahiro Kinoshita; Hideo Yoshida; Tomoro Hishiki (Elsevier, 2020)
Background: Esophageal leiomyomatosis (EL) is a rare benign tumor defined as a diffuse form of marked hypertrophy in the muscular layer of the esophagus. Relapses have been reported as a result of misdiagnoses of other tumors or achalasia, followed by inappropriate surgical intervention. The endoscopic approach is preferred because of its lesser degree of invasiveness and better cosmesis; however, its effectiveness for treatment of EL is unclear because these tumors are bulkier and more extensive than those in other esophageal diseases. Case presentation: We treated an 11-year-old girl who had been experiencing progressive dysphagia, vomiting, and coughing during sleep since the age of 4 years and was correctly diagnosed with EL using computed tomography and endoscopic ultrasonography. She was successfully treated with total minimally invasive esophagectomy (MIE), combining thoracoscopy and laparoscopy, in the prone position, without any complications or recurrence of symptoms. To our knowledge, this is the first case report of MIE for EL. A review of 84 EL cases (including the present case) revealed a rate of accurate preoperative diagnosis of only 23.8%. Esophagectomy should be employed because the recurrence rate of the non-esophagectomy cases, involving myotomy and tumorectomy, was significantly higher than that of the esophagectomy cases (57.9% vs. 7.7%, p = 0.002). Among 11 relapse cases in the non-esophagectomy cases, esophagectomy was performed in eight. Among the four relapse cases in the esophagectomy group, additional esophagectomy was necessary in three because of insufficient resection of the tumors at the primary esophagectomy. Conclusions: Multimodal imaging contributes to accurate diagnosis and assessment of the extent of the tumors, thus leading to the selection of the appropriate surgical intervention, i.e., radical esophagectomy. Total MIE in the prone position provides excellent exposure of the operative fields; our experience suggests that total MIE is beneficial for EL, as it is for other esophageal tumors. Keywords: Esophageal leiomyomatosis, Minimally invasive esophagectomy, Prone position, Achalasia, Case report, Review of literature